2015
DOI: 10.1016/j.cmet.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

snoRNA U17 Regulates Cellular Cholesterol Trafficking

Abstract: Summary Cholesterol is required for the growth and viability of mammalian cells, and is an obligate precursor for steroid hormone synthesis. Using a loss-of-function screen for mutants with defects in intracellular cholesterol trafficking, a Chinese hamster ovary cell mutant with haploinsufficiency of the U17 snoRNA was isolated. U17 is a H/ACA orphan snoRNA, for which a function other than ribosomal processing has not previously been identified. Through expression profiling, we identified hypoxia upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Intriguingly, this hypothesis is favored by recent studies that established an emerging role of snoRNAs in specific metabolic functions. A striking example is that of U17, a dyskerin binding snoRNA involved in intracellular cholesterol trafficking . Worth noting, proper sorting and trafficking within endosomal vesicles is necessary to maintain cellular homeostasis and to perform both ubiquitous and cell type‐specific functions.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, this hypothesis is favored by recent studies that established an emerging role of snoRNAs in specific metabolic functions. A striking example is that of U17, a dyskerin binding snoRNA involved in intracellular cholesterol trafficking . Worth noting, proper sorting and trafficking within endosomal vesicles is necessary to maintain cellular homeostasis and to perform both ubiquitous and cell type‐specific functions.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria associated membranes are also rich in cholesterol and in the simple sphingolipid ceramide (106). An outer mitochondrial membrane adaptor protein, hypoxia-upregulated mitochondrial movement regulator (HUMMR), increases the ER-mitochondria MCSs to facilitate cholesterol flux to mitochondria (107). Interestingly, studies in a mouse model for Alzheimer's disease (AD) showed that, in the early stage of AD development, synaptic mitochondria exhibit significant functional deficits; the degree of deficits correlates positively with amyloid- (A) peptide accumulation (108).…”
Section: The Three Cholesterol Trafficking Routes In a Mammalian Cellmentioning
confidence: 99%
“…In the same way, Brandis et al [52] has shown that the box C/D snoRNA U60 regulates intracellular cholesterol trafficking between the plasma membrane and the endoplasmic reticulum. Similarly, the snoRNA U17 regulates the cellular cholesterol trafficking through the hypoxia-upregulated mitochondrial regulator (HUMMR) by acting on its target mRNA [53]. Here, the modification of the level of the h-jou, either its overexpression or its depletion leads to a strong deregulation of metabolic pathways as revealed by the KEGG analysis (about 400 genes).…”
Section: Discussionmentioning
confidence: 99%